Indocyanine green clearance test as a predictor of chemotherapy liver toxicity and post-operative complications in patients with colorectal liver metastases - Sergio Cortese (Cirugía y Cirujanos, 2022)
Objective: This study aims to investigate the relationship between the pre-operative indocyanine green (ICG) test, the chemotherapy- associated liver injury (CALI), and the development of severe post-operative complications (POC) in patients operated of colorectal liver metastases (CRLMs). Materials and methods: Sixty-nine patients previously treated with chemotherapy and submitted to liver resection for CRLM were retrospectively studied. Two pathologists independently reviewed the pathological specimens and assessed the presence of CALI. The correlation between ICG clearance and specific pathological features was analyzed. In addition, a logistic regression analysis was performed to seek for pre-operative factors associated with severe complications. Results: After a mean of 10.6 (± 7.5) chemotherapy cycles, 44 patients (63.8%) developed CALI. ICG retention rate at 15 min (ICG-R15) was not statistically different between patients with and without CALI and it could only discriminate the presence of centrilobular fibrosis. Rate of severe complications was almost 6-fold in patients with CALI compared to patients without CALI (p = 0.024). ICG-R15 ≥ 10% was the only independent risk factor associated with severe POC at multivariable logistic regression (OR = 4.075 95%CI: 1.077-15.422, p = 0.039). Conclusions: Pre-operative ICG clearance test, although not useful to identify patients with hepatic drug toxicity, is a strong predictor for the development of severe post-hepatectomy complications.